Advancing Circular Fashion: An Innovative Reuse Framework for Knit Denim Garments via Cold Bleaching, Dry Processing and Bio-polishing - Hossain, Amjad; Rahman, Mahbubur; Alam Shakil, S. M. Mahbubul; Mitu, Sharmin Akter; Chowdhury Rubel, Maniruzzaman (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
This study investigates the feasibility of fostering the sustainability of used knit denim through an integrated upcycling approach involving cold bleaching, dry processing, bio-polishing, and softening. This research is oriented toward reducing water consumption, chemical waste, and textile landfill contributions. The study also evaluates how well upcycled denim performs both physically and chemically in large-scale manufacturing settings. A sample of worn knit denim pants was cleaned with detergent and treated sequentially with eco-friendly processes: cold bleaching (using calcium hypochlorite), dry mechanical techniques (e.g., PP spray for localized fading), enzymatic bio-polishing to reduce fiber pilling, and softening agents to improve tactile quality. Data were analyzed through comparative assessments of tearing strength, color fastness (to wash, perspiration, and rubbing), pH levels, and GSM (grams per square meter). Results revealed that the upcycled denim performed well in terms of color retention, with post-treatment ratings of 4–5 (on a 5-point scale) across acid/alkaline perspiration and washing tests, compared to pre-treatment values of 3–4. Tearing strength improved by 14% in the warp direction (from 17.2 N to 19.6 N) and 28% in the weft direction (from 62 N to 79.8 N), which indicated improved durability. The pH remained within safe ranges (7.2 post-wash), and GSM changes were minimal (498 to 484.6), preserving fabric integrity. Visual assessments confirmed restored aesthetic appeal, while cost analysis pointed to practical industrial use at 1.89 per unit. By integrating water-saving and low-energy processes, this work proposes a scalable framework to prolong the lifecycle of knit denim, mitigate textile waste, and promote sustainable circular fashion practices. The findings highlight the possibility of combining cold bleaching with enzymatic treatments to balance sustainability with market competitiveness, offering effective solutions for the denim industry.